Trigeminal neuralgia and persistent idiopathic facial pain - Obermann, Mark; Holle, Dagny; Katsarava, Zaza (Headache Medicine, 2012)
Trigeminal neuralgia (TN) and persistent idiopathic facial pain (PIFP) are two of the most puzzling orofacial pain conditions and affected patients often are very difficult to treat. TN is characterized by paroxysms of brief but crucial pain, followed by asymptomatic periods without pain. In some patients a constant dull background pain may persist. This constant dull pain sometimes makes the distinction from PIFP difficult. PIFP is defined as continuous facial pain, typically localized in a circumscribed area of the face, which is not accompanied by any neurological or other lesion identified by clinical examination or clinical investigations. The pain usually does not stay within the usual anatomic boundaries of the trigeminal nerve distribution and is a diagnosis of exclusion. Epidemiologic evidence on TN and even more so on PIFP is quite scarce, but generally both conditions are considered to be rare diseases. The aetiology and underlying pathophysiology of TN and more so PIFP remain unknown. Treatment is based on only few randomized controlled clinical trials and insufficiently evaluated surgical procedures.